(untitled) (Art of Medicine, 2023)
Cutis verticis gyrata (CVG) is a descriptive term for a rare benign skin condition characterized by the formation of tortuous folds and deep furrows that mimic the gyri of the brain because of excessive skin growth. It is observed mainly in men. The first clinical case of the disease was described in 1837 by Alibert J. There are primary and secondary forms of CVG. Among the cases of primary CVG in 1984, Garden JM and Robinson JK further distinguished the essential and combined subtypes. The reason for the appearance of the essential form is not known. Primary combined CVG can accompany neuropsychiatric disorders, cerebral palsy, epilepsy, seizures, and ophthalmological abnormalities, most commonly cataracts. Secondary CVG occurs as a result of chronic inflammation, such as hysteria, lymphostasis, elephantiasis, eczema, psoriasis, folliculitis, atopic dermatitis, etc. In case of secondary CVG, the lower extremities are more often affected, the skin is congested-red, cyanotic, dense, swollen. Papillomatous growths, layering of crusts and scales are often visible against the background of changed skin. Given the rarity of this disease (it was diagnosed for the first time in our more than 50 years of dermatological practice), we report a clinical case of CVG. Case Presentation. Patient P., 27 years old, complained of wrinkles and increased mobility of the skin of the scalp. He noticed the first manifestations of the disease at the age of 17, but did not pay attention, believing that these were individual features of the skin structure. For the last 3-4 years in a row, he noticed a thickening and increase in the size of the folds of the skin on the scalp, growing mobility. The skin, according to the patient, had the appearance of ribs. During the dermatological examination, the skin is of normal color, turgor and elasticity are preserved, sweat and sebum secretion is moderate. Skin appendages are without pathological changes. The skin of the scalp is uniformly covered with thick hair, hyperelastic, pronounced transverse deep linear furrows resembling brain convolutions are visible. When using dermoscopy without a light-conducting liquid, the vascular pattern is hardly visible, on the surface there is small lamellar peeling. However, after its application, areas of clearly visible vessels of the superficial vascular plexus of the skin, which coincide with the location of the furrows, are determined. The patient was examined; no pathology was detected on the part of internal organs and heart. The results of ultrasound of the thyroid gland and organs of the abdominal cavity were without pathological changes. General analysis of blood, urine, blood sugar within the normal range. Biochemical indicators of liver and kidney function without deviations. The patient is recommended to have a periodic examination by a dermatologist. With increasing clinical manifestations - surgical removal of skin folds. Conclusions. The described clinical case of CVG is of considerable interest to dermatologists, pediatricians, and geneticists as a rare new developmental disease. In our report, the clinical picture of changes on the skin is illustrated, and differential diagnosis with dermatoses that are closest in clinical manifestations is briefly carried out.